Ameliorating Students’ Cognitive Engagement and Critical Thinking in Chemistry: Testing the Potency of Practical-Based and Discussion-Based (British Journal of Multidisciplinary and Advanced Studies, 2025)
This research investigated if either Practical-Based Approach (PBA) or Discussion-Based Approach (DBA) could be more effective in ameliorating students’ cognitive engagement and critical thinking ability in Chemistry. The study adopted a quasi-experimental research design. Chemistry Cognitive Engagement Inventory (CCEI) and Critical Thinking Ability Test (CTAT) were the instruments used for data collection. The reliability index of CCEI was ascertained using Cronbach Alpha, which gave reliability value of 0.86. The internal consistency of CTAT was tested using Kuder-Richardson (KR-21) formula which yielded a reliability value of 0.92. The population is 6,837 SS2 students offering chemistry in SSS in Dekina Local Government Area of Kogi State, Nigeria. Using multi-stage sampling techniques, a sample of 166 students drawn from 4 schools in Dekina LGA was selected. Two research questions and four null hypotheses guided the study. The research questions were answered using Mean and Standard Deviation scores while the null hypotheses were tested at 0.05 level of significance using results from Analysis of Covariance (ANCOVA). The study revealed that, the difference in the cognitive engagement and critical thinking ability of students taught chemistry using PBA and those taught using DBA was statistically significant in favour of PBA respectively {F1, 165 =138.100, P0.05}. It was recommended among others that; Chemistry teachers should be encouraged to use PBA during chemistry instruction to ameliorate students’ cognitive engagement and critical thinking ability.